Auxin-Inducible Degron System Reveals Temporal-Spatial Roles of HSF-1 and Its Transcriptional Program in Lifespan Assurance - Morphis, Allison C.; Edwards, Stacey L.; Erdenebat, Purevsuren; Kumar, Lalit; Li, Jian (Frontiers in Aging, 2022)
HSF-1 is a key regulator of cellular proteotoxic stress response and required for animal lifespan. In C. elegans, HSF-1 mediated heat shock response (HSR) declines sharply on the first day of adulthood, and HSF-1 was proposed to function primarily during larval stages for lifespan assurance based on studies using RNAi. The tissue requirement for HSF-1 in lifespan, however, is not well understood. Using auxin-inducible degron (AID) system, we manage to uncouple the roles of HSF-1 in development and longevity. We find in wild-type animals HSF-1 is required during the whole self-reproductive period for lifespan. This period is extended in long-lived animals that have arrested germline stem cells (GSC) or reduced insulin/IGF-1 signaling (IIS). While depletion of HSF-1 from any major somatic tissues during development results in severe defects, HSF-1 primarily functions in the intestine and likely neural system of adults to support lifespan. Finally, by combining AID and genome-wide transcriptional analyses, we find HSF-1 directly activates transcription of constitutively-expressed chaperone and co-chaperone genes among others in early adulthood, which underlies its roles in longevity assurance.